1
$\begingroup$

Consider:

$$ n_k = [\frac{(k-1)(1-\rho)}{1 + (1-\rho)k}][\frac{(k-2)(1-\rho)}{1 + (1-\rho)(k-1)}]... $$

Where $k \geq 1$ and $0 < \rho < 1$. My interpretation is:

$$ \frac{(1-\rho)^{k-1}}{(1-\rho)^k}[\frac{(k-1)}{(\frac{1}{1-\rho}+k)}][\frac{(k-2)}{(\frac{1}{1-\rho}+(k-1))}]... $$

But I think I am missing something.

$\endgroup$
0
$\begingroup$

Let's assume $\rho \neq 1$ and $k\geq 2$. Each factor of $n_k$ has the shape \begin{align*} \frac{(j-1)(1-\rho)}{1+(1-\rho)j}=\frac{1-\rho}{1-\rho}\cdot \frac{j-1}{\frac{1}{1-\rho}+j}=\frac{j-1}{\frac{1}{1-\rho}+j}\qquad\qquad 2\leq j \leq k \end{align*}

We obtain using the product symbol \begin{align*} n_k=\prod_{j=2}^k\frac{(j-1)(1-\rho)}{1+(1-\rho)j}=\prod_{j=2}^k\frac{j-1}{\frac{1}{1-\rho}+j} =(k-1)!\prod_{j=2}^k\frac{1}{\frac{1}{1-\rho}+j} \end{align*}

Hint: The problem is not clearly specified. To fully state the problem we need to know assertions like $\rho \neq 1$ and ranges of variables ($k\geq 2$). We should also specify that the rightmost factor of $n_k$ is $\frac{1\cdot(1-\rho)}{1+(1-\rho)\cdot2}$ to indicate that we don't want a factor $0$ to be part of this product.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.